Pengetahuan, Sikap dan Dukungan Sosial Berkaitan dengan Keikutsertaan Masyarakat pada Program Vaksinasi COVID-19 di Tulehu, Maluku Tengah - Elpira Asmin; Mahusein Tuharea; Halidah Rahawarin (Jurnal Kesehatan Komunitas, 2023)
Data on vaccination coverage in Central Maluku Regency is the Regency with the second lowest percentage after West Seram. Tulehu Village is one of two villages with low vaccination rates in Salahutu District with a vaccine percentage of 35.59%. The purpose of this study was to analyze the relationship between knowledge, attitudes, and social support with community participation in COVID-19 vaccination in Tulehu Village, Central Maluku Regency in 2022. This study was a quantitative analytical study with a cross-sectional approach and a sample of 106 respondents. This research uses a purposive sampling technique. The results of the research conducted showed a relationship between knowledge (p = 0.022), attitude (p = 0.048), and social support with community participation in Tulehu Village in the COVID-19 vaccination program (p = 0.027). The results of this study indicate a relationship between the dependent and independent variables. These results can be concluded that the better a person's knowledge, attitudes, and social support, the better one's participation in the COVID-19 vaccination will be. It is recommended to increase education and support to the community regarding COVID-19 vaccination.